Transport and environment in search of sustainable solutions - Feitelson, Eran, 1956-; Verhoef, Erik T.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2001)
The impact of transport on the environment is a major issue of worldwide concern. This important new book presents state-of-the-art contributions on spatial and technological aspects of transport in relation to environmental degradation, together with analysis of sustainable transport policy.
pt. 1. Policy aspects -- pt. 2. Technological aspects -- pt. 3. Spatial aspects.
Includes bibliographical references and index.
Keywords: Transportation -- Environmental aspects; Sustainable development; Electronic books